Reproducibility of soft tissue cephalometric landmark identification by conventional and digital direct radiography - Bonilla-Londoño, Margarita María; Barrera-Chaparro, Judith Patricia; Arroyave-Godoy, Ángela Patricia; Díaz-Roa, Mónica Eliana (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: there is little information on the reproducibility of soft tissue cephalometric points; the purpose of this study was then to evaluate the reproducibility and accuracy of soft tissue cephalometric landmark identification in direct digital radiography and conventional radiography. Methods: 11 pairs of conventional and direct digital radiographs were introduced in the Cephapoint program. 10 cephalometric points were located on a Cartesian plane (X and Y) in conventional and digital images. The measurements were taken twice by 3 operators with 1 week interval. Interobserver average error was calculated in order to assess reproducibility in each point, and intraobserver error was used to determine accuracy. Results: interobserver error in soft tissue cephalometric points was less than 1 mm for most points in both images, except in chin and pogonion, with no statistically significant differences. Statistically significant differences were found between the variances in the X axis, with less variability in the case of digital radiography in these points: labrale superius (p = 0.043), subnasale (p = 0, 013), columella (p = 0.038), stomion superius (p = 0.029), and stomion inferius (p = 0.015). The Y axis did not show statistically significant differences between the two methods. The assessment of intraobserver reproducibility showed an excellent Intraclass Correlation Coefficient (ICC) (0.935) in both methods. Conclusion: according to the findings of this study, the evaluated radiographs and methods offer similar diagnostic accuracy.